THEORETICAL ASPECTS REGARDING THE APPLICATION OF TREATIES IN TIME AND SPACE - Roxana-Mariana POPESCU (Challenges of the Knowledge Society)
Treaties in force, more precisely those not affected by a cause of nullity or not expired, must be applied by the parties in good faith. The application of a treaty implies the obligation to introduce it into the internal legal order of each state party and raises the issue of the relationship between international law and the internal law of the states. The application in time of treaties is governed by the principle of non-retroactivity of conventional provisions. In principle, a treaty is applied on the territory or with regard to the territory of the contracting parties. There are, however, cases in which the treaty can only be applied to a part of their territory or it can have an „ultra-territorial” application, that is, it is intended to be applied on the territory of third countries.